A profile-based Big data architecture for agricultural context - Soumaya Lamrhari; Hamid Elghazi; Tayeb Sadiki; Abdellatif El Faker (2016 International Conference on Electrical and Information Technologies (ICEIT), 2016)
Bringing Big data technologies into agriculture presents a significant challenge; at the same time, this technology contributes effectively in many countries’ economic and social development. In this work, we will study environmental data provided by precision agriculture information technologies, which represents a crucial source of data in need of being wisely managed and analyzed with appropriate methods and tools in order to extract the meaningful information. Our main purpose through this paper is to propose an effective Big data architecture based on profiling system which can assist (among others) producers, consulting companies, public bodies and research laboratories to make better decisions by providing them real time data processing, and a dynamic big data service composition method, to enhance and monitor the agricultural productivity. Thus, improve their traditional decisionmaking process, and allow better management of the natural resources
Keywords: Big data; precision agriculture; profiling system; decision making